Rancang Bangun Transmitter Gigabit WLAN - Wahyul Amien Syafei; Imam Santoso; Hayu Pratista (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
Wireless LAN is wireless technology that can be used for voice and data communication. The increase of user requirement in Wireless LAN system caused the development of Wireless LAN increasing too. Standard of Wireless LAN is IEEE802.11a/b/g and IEEE802.11n use OFDM and MIMO technique for increase data rate without additional bandwidth. The purpose of this final project is to design physical layer of transmitter wireless LAN system to obtain gigabit throughput. Wireless LAN that we used now can produce rate up to 600 Mbps. So we expect this design of wireless system can increase data rate into gigabit throughput. The design of this system organized from arrangement of block diagram into preamble and data field. The data field, same as the previous standard, 802.11n consists of block scrambler, encoder parser, FEC encoder, interleaving, constellation mapper, spatial mapper, IFFT, cyclic shift, guard interval inserter and windowing. Whereas the preamble consists of legacy preamble is L-STF, L-LTF and L-SIG that have same format with previous standard in order to the output of transmitter 802.11ac can be compatible to 802.11a/n. Then, very high throughput preamble is added to this system as a preamble for 802.11ac. From the experiment result, we get the conclusion that wireless LAN 802.11ac is formed based on the previous standard 802.11a and 802.11n which have same frequency 5 GHz. Then, for 802.11ac we duplicate bandwidth from 40 MHz to 80 MHz and apply phase rotation. For the software verification backward compatibility, we determine the parameters 100 iteration, use MCS (Modulation Coding Scheme) 64-QAM and 4 transmit antenna. As the result the 802.11ac transmitter can be recognized by 802.11a/n receiver and it can be shown as decreasing of SIG Error rate for SNR range 0-20 dB. Key words : Wireless LAN, IEEE802.11a/n, Gigabit throughput, Backward compatibility